Detection of Rift Valley Fever Virus Lineage H From South Africa Through the Syndromic Sentinel Surveillance Network in Senegal. (29th December 2021) - Bob, Ndeye Sakha; Barry, Mamadou Aliou; Diagne, Moussa Moise; Faye, Martin; Ndione, Marie Henriette Dior; Diallo, Amadou; Diop, Mamadou; Diop, Boly; Faye, Oumar; Loucoubar, Cheikh; Fall, Gamou; Faye, Ousmane
Abstract: Background: Rift Valley fever virus (RVFV) is an arbovirus that causes epizootics and epidemics among livestock population and humans. Our surveillance system has revealed multiple emergences and re-emergences of RVFV in West Africa over the last decade. Methods: The Sentinel Syndromic Surveillance Network in Senegal (4S) has been implemented since 2011. Samples from human suspected arbovirus infection in 4S sentinel sites were sent to Institut Pasteur de Dakar (IPD), where arbovirus diagnosis by enzyme-linked immunosorbent assay (ELISA), real-time reverse transcription polymerase chain reaction (RT-PCR), and virus isolation was performed. Overall, IPD has received a total of 1149 samples from arboviral suspected patients through the 4S network from January to December 2020. These samples were screened for 7 arboviruses including RVFV. Whole-genome sequencing of positive RVFV samples by RT-PCR was performed using the Illumina Miseq platform followed by genome assembly. Phylogenetic analyses were performed using MEGA X. Results: Out of the 1149 arbovirus suspected cases, 4 RVFV-positive samples were detected with RT-PCR while 5 RVFV-positive samples were detected by ELISA. Complete genome sequences were obtained for 3 strains among the 4 positive samples by RT-PCR. Phylogenetic analyses indicated an emergence of a virus first described in South Africa during a major outbreak. Conclusions: This strong surveillance system allowed the detection of an RVFV outbreak in Senegal in 2020. The obtained genomes clustered with strains from South Africa belonging to lineage H. This calls for implementation of a strong surveillance system for wild animals, humans, and livestock simultaneously in all African countries. Abstract : D/C/F/TAF is the reference for combination therapy based on protease inhibitors but has not been compared with regimens containing integrase inhibitors as initial ART. We could not demonstrate D/C/F/TAF noninferiority relative to DTG/ABC/3TC, although both regimens were similarly well tolerated.